Estudio de pre factibilidad para la integración de funciones domóticas en las residencias Ap Kacuna (2022)
This degree work seeks to establish the technical and financial aspects of the integration of home automation systems in the AP KACUNA residential complex and to dimension the energy saving supervised by a low voltage distribution network until the interior installation of the house, complying with all regulations current legal regulations. The objective was Carry out a prefeasibility study for the integration of home automation functions in AP KACUNA residences.